2021
DOI: 10.1111/jgh.15395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia‐inducible factor‐1α and hypoxia‐inducible factor‐2α overexpression on hepatocellular carcinoma survival: A systematic review with meta‐analysis

Abstract: Background and Aim The role of hypoxia‐inducible factor‐1α (HIF‐1α) and hypoxia‐inducible factor‐2α (HIF‐2α) has been implicated in the clinical prognosis of hepatocellular carcinoma (HCC), but the results remain controversial. We aim to investigate the association of HIF‐1α and HIF‐2α overexpression with the prognosis and clinicopathological features of HCC. Methods A systematic search was conducted in PubMed, Embase, Scopus, Web of Science, and Cochrane Library until June 20, 2020. Meta‐analysis was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…The present results demonstrated that the HIF1α-VEGF-C axis was upregulated by increased Jnk1 mRNA and JNK expression by the FA-rich diets in HCVcpTg mice. Overexpressions of JNK1 and HIF1α have been detected in human HCC samples and were correlated with unfavorable patient outcomes [62, 63]. FA reportedly activated JNK through SRC non-receptor tyrosine kinase and might be related to the Warburg effect [60, 64]; however, the precise mechanism of how FA enhances Jnk1 mRNA expression requires clarification in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The present results demonstrated that the HIF1α-VEGF-C axis was upregulated by increased Jnk1 mRNA and JNK expression by the FA-rich diets in HCVcpTg mice. Overexpressions of JNK1 and HIF1α have been detected in human HCC samples and were correlated with unfavorable patient outcomes [62, 63]. FA reportedly activated JNK through SRC non-receptor tyrosine kinase and might be related to the Warburg effect [60, 64]; however, the precise mechanism of how FA enhances Jnk1 mRNA expression requires clarification in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of HIF-1α was also associated with clinicopathologic features including BCLC, intrahepatic metastasis, lymph node metastasis, tumor-to-lymph node metastasis (TNM), tumor differentiation, tumor number, tumor size, vascular invasion, and angiogenesis (5). Another meta-analysis involving 3,238 patients in 22 studies also showed poor prognosis in HCC patients presenting with overexpression of HIF-1α (45). However, other studies showed that HIF-1α protein expression was associated with tumor differentiation, and intrahepatic and extrahepatic metastases, but not with the presence of portal vein tumor embolism, prognosis, or hepatitis B surface antigen (HBsAg) status (41).…”
Section: Expression and Prognosis Of Hif-1α In Hepatocellular Carcinomamentioning
confidence: 95%
“…In fact, the expression of the most important rate limiting enzymes involved in glycolysis is frequently altered in liver cancer [23]. Most of these genes are regulated by the O 2sensitive transcription factor hypoxia inducible factor 1 (HIF1α) that was reported to be stabilized and activated in HCCs [24]. Of note, HIF1α also regulates the expression of the glucose transporter GLUT1 which resulted to be upregulated in HCC and to be associated with tumor histological grade [25].…”
Section: Glycolysismentioning
confidence: 99%